Progress in Atomically Precise Coinage Metal Clusters with Aggregation‐Induced Emission and Circularly Polarized Luminescence - Zhang, Miao‐Miao; Li, Kai; Zang, Shuang‐Quan (Advanced optical materials, 2020)
Materials with circularly polarized luminescence (CPL) are especially fascinating due to the widespread potential applications in 3D displays, biological probes, security encoding, encrypted information transmission, and storage. Among these CPL‐active materials, the ones based on atomically precise coinage, namely, the metal coinage clusters, have attracted increasing attention due to their fascinating chiral structures and intriguing luminescence characteristics. Meanwhile, these clusters provide an ideal platform at the nanoscale for understanding the chiral transfer across the organic–inorganic interface. In this report, the recent progress in constructing enantiomerically pure chiral coinage metal clusters and the luminescent mechanism of coinage metal clusters in aggregated state are reviewed, respectively. Moreover, CPL‐active atomically precise coinage metal clusters and their design strategies are discussed in detail. Finally, challenges and opportunities for constructing atomically precise coinage metal clusters with excellent CPL properties are discussed. The development of circularly polarized luminescence (CPL)‐active materials has attracted increasing attention due to their wide potential applications. In this work, the design strategies for chiral and luminescent coinage metal clusters are summarized. Then, the research progress in the CPL‐active atomically precise coinage metal clusters is reviewed. The potential directions and challenges for future research are discussed.